Rates of Tobacco Use Disorder, Pharmacologic Treatment, and Associated Mental Health Disorders in a Medicaid Claim Review Among Youth in Indiana, USA. (5th August 2022) - McBrayer, Kimberly; Ouyang, Fangqian; Adams, Zachary; Hulvershorn, Leslie; Aalsma, Matthew C.
Purpose: This study delineates a number of Medicaid youth with tobacco use disorder (TUD), prescribing habits for treatment, and associated externalizing disorders. Methods: Youth Medicaid claims from 2007-2017 processed in a large Midwestern city were analyzed for a diagnosis of TUD, related pharmacotherapy, and externalizing mental health and substance use disorders. Results: Claims connected 6541 patients with 42 890 visits. Mean age was 16.4 with 40% female. 1232 of the 6541 charts contained a TUD diagnosis equating to 1848 visits. A comorbid diagnosis of ADHD, cannabis use, and conduct disorder were more common in males (3.9% vs 1.3% in females; 3.4% vs .8%; and 2.8% vs .8%; P < .05). 808 scripts were provided to 152 of the 1232 youths, with 4.7% of those scripts a nicotine replacement product. Conclusions: Pharmacotherapy is underutilized in this Medicaid claims data set. Certain externalizing factors were associated with males with TUD more than females.